PURITANICAL CHALLENGES IN ARTHUR MILLER’S “THE CRUCIBLE”. - Arunakumari , S (International Journal of Psychosocial Rehabilitation, 2021)
The Crucible, a play by Arthur Miller, was an adaptation of the Salem witch trials, whichtook place in the American province of Massachusetts Bay in 1692 and 1693. In theCrucible's play, all characters are all based on real people who lived in Salem. Althoughthere are several similarities to our own time in the play, it is full of ideas and attitudes thatwere unique to Salem, Massachusetts, in 1692. To clearly understand the play, someknowledge of Salem is required. As a result, the following information discusses essentialPuritan beliefs and customs, as well as history including its historical Salem witch trials. Inparticular, Miller's use of such Salem witch trials to critique upon this McCarthy trials in the1950s discussed all these things throughout this paper.